2017
DOI: 10.1007/s11356-016-8351-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration pattern and induced apoptosis of bisphenol A in zebrafish embryos at environmentally relevant concentrations

Abstract: Bisphenol A (BPA) is a well-known endocrine-disrupting chemical that is ubiquitously present in the environment. In the present study, 4-h post-fertilization (hpf) zebrafish embryos were exposed to various environmentally relevant concentrations of BPA (0.1, 1, 10, 100, and 1000 μg/L) until 72 and 168 hpf, and the accumulation pattern of BPA and its potential to induce toxicity through apoptosis were determined. Compared to BPA concentrations in larvae at 168 hpf, BPA concentrations in embryos exposed until 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Comparing BPA uptake to E2 uptake can further inform future studies using nonsteroidal EDCs. While research testing the effects of BPA on development are abundant, many of these studies use environmentally-relevant low nanomolar concentrations of BPA in treatment water (Kinch et al, 2015; Kinch et al, 2016; Saili et al, 2012; Wu et al, 2017). Based on our results, the amount of BPA available to the embryo is substantially less than the reported EC 50 of BPA for the zebrafish estrogen receptors ERα, 599 nM, ERβ1, 18.9 µM, and ERβ2, 3.8 µM Another explanation for BPA effects at nanomolar concentrations is that BPA prevents the binding of endogenous estrogens to their receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing BPA uptake to E2 uptake can further inform future studies using nonsteroidal EDCs. While research testing the effects of BPA on development are abundant, many of these studies use environmentally-relevant low nanomolar concentrations of BPA in treatment water (Kinch et al, 2015; Kinch et al, 2016; Saili et al, 2012; Wu et al, 2017). Based on our results, the amount of BPA available to the embryo is substantially less than the reported EC 50 of BPA for the zebrafish estrogen receptors ERα, 599 nM, ERβ1, 18.9 µM, and ERβ2, 3.8 µM Another explanation for BPA effects at nanomolar concentrations is that BPA prevents the binding of endogenous estrogens to their receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Wu and colleagues also used HPLC-MS to measure BPA uptake in zebrafish embryos from 4–72 hpf with multiple exposure concentrations (Wu et al, 2017). Comparing their 1 µg/L exposure (4.38 nM) to our 5 nM treatment from 48–72 hpf yields similar results, with 0.196 pmol/embryo via HPLC, and 0.190 pmol/embryo via our isotopic assay.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing BPA uptake to E2 uptake can further inform future studies using nonsteroidal EEDs. While research testing the effects of BPA on development are abundant, many of these studies use environmentally-relevant low nanomolar concentrations of BPA in treatment water (Kinch et al, 2015; Kinch et al, 2016; Saili et al, 2012; Wu et al, 2017). Based on our results, the amount of BPA available to the embryo is substantially less than the reported EC 50 of BPA for the zebrafish estrogen receptors ERα, 599 nM, ERβ1, 18.9 μM, and ERβ2, 3.8 μM (Pinto et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Wu and colleagues also used HPLC-MS to measure BPA uptake in zebrafish embryos from 4-72 hpf with multiple exposure concentrations (Wu et al, 2017). Comparing their 1 μg/L exposure (4.38 nM) to our 5 nM treatment from 48-72 hpf yields similar results, with 0.196 pmol/embryo via HPLC, and 0.190 pmol/embryo via our isotopic assay.…”
Section: Discussionmentioning
confidence: 99%
“…For the DEGs with EC between 0.001~0.01µM, only apoptosis relevant FOXO signaling pathway (FDR= 0.057, covered 4 genes) was enriched. Previous research reported BPA could induced apoptosis of mice spermatocytes 51 and zebrafish embryo 52 . A larger number of pathways, which included liver development, regulation of nucleobase-containing compound metabolic process, sensory organ morphogenesis, and DNA binding, were associated with the DEGs with EC between 0.01~0.1µM.…”
Section: Molecular Profiling Of Zebrafish Exposed To Bpamentioning
confidence: 91%